Neurophysiological correlates of attentional fluctuation in attention-deficit/hyperactivity disorder - Cheung, Celeste H. M.; Brandeis, Daniel; Banaschewski, Tobias (Brain topography, 2017)
Cognitive performance in attention-deficit/hyperactivity disorder (ADHD) is characterised, in part, by frequent fluctuations in response speed, resulting in high reaction time variability (RTV). RTV captures a large proportion of the genetic risk in ADHD but, importantly, is malleable, improving significantly in a fast-paced, rewarded task condition. Using the temporal precision offered by event-related potentials (ERPs), we aimed to examine the neurophysiological measures of attention allocation (P3 amplitudes) and preparation (contingent negative variation, CNV), and their associations with the fluctuating RT performance and its improvement in ADHD. 93 participants with ADHD and 174 controls completed the baseline and fast-incentive conditions of a four-choice reaction time task, while EEG was simultaneously recorded. Compared to controls, individuals with ADHD showed both increased RTV and reduced P3 amplitudes during performance on the RT task. In the participants with ADHD, attenuated P3 amplitudes were significantly associated with high RTV, and the increase in P3 amplitudes from a slow baseline to a fast-paced, rewarded condition was significantly associated with the RTV decrease. Yet, the individuals with ADHD did not show the same increase in CNV from baseline to fast-incentive condition as observed in controls. ADHD is associated both with a neurophysiological impairment of attention allocation (P3 amplitudes) and an inability to adjust the preparatory state (CNV) in a changed context. Our findings suggest that both neurophysiological and cognitive performance measures of attention are malleable in ADHD, which are potential targets for non-pharmacological interventions.
Gesehen am 25.04.2018